Design and Evaluation of K-Pass: A Bicycle-Friendly Modification of Speed Bumps. Issue 36 (December 2018) - Vasudevan, Vinod; Rajurkar, Aniruddha; Soni, Rahul; Tiwari, Akhil
Traffic safety is a major concern across the world. Since speed is a major cause of traffic crashes, various traffic calming measures are used to enhance the safety of the road users in urban areas. Speed humps and bumps are the most widely used traffic calming devices. As a considerable number of bicyclists use the road along with motorized users, it is important to consider them while deploying any traffic calming devices. Studies have shown that bicyclists experience significantly larger discomfort as compared to motorized vehicles while passing over speed humps. In this study, a modification has been proposed to enhance riding comfort of bicyclists without compromising the traffic calming attribute of a speed bump. This modification is named "K-pass." Analysis of data collected before and after the modification justifies the effectiveness in reducing the discomfort of bicyclists. Over a period of eight months, 70% of the bicyclists chose to use K-pass. Data also revealed that a high proportion of motorized two-wheeler users also used the K-pass at reduced speeds. It is expected that the K-pass will be a useful modification to the existing speed humps and speed bumps in areas where bicycle usage is expected.